Avaliação de usabilidade de um monitor multiparamétrico utilizado em um estabelecimento assistencial de saúde público - Barreto, Cassiana Gabriela Lima (2018)
Nowadays, health care establishment (HCE) have increasingly incorporated technologies, among which are medical assistance equipment (MAE). MAEs have great relevance in patient care and have interfaces ranging from the simplest to those with a high degree of complexity. However, for technology to perform its role adequately it is essential that the health professional is able to operate them safely and effectively and has satisfaction in using it. In this sense, the evaluation of the interaction, use and knowledge of the technology must be evaluated. Usability is a tool that has often been used for this purpose. Thus, the objective of this study was to perform a comparative study of the Usability of a medical-assistance equipment (MAE), between sectors of a large public HCE and high complexity. The MAE used in this study was a multi-parameter monitor. The evaluation of Usability of the MAE consisted in the application of three combined tools: Usability Test Protocol, Data Collection Instrument and Evaluation Control. We verified the linear relationship between the factors that interfere with the Usability of the equipment as well as the Usability problems of the monitor presented by the group of participants (30 users) who performed the Usability Test. The efficiency, effectiveness and satisfaction generated by the equipment in the users were also studied. As a result, it was verified that there is no statistical difference of the Usability of the equipment between the sectors under study, that is, the perceived Usability of the equipment is the same in all sectors. It was also verified that the main Usability problems for this sample were: configuration, identity and handling problems. In addition, it was possible to verify that all factors Familiarity, Expertise, Attitude and Utility, corroborate to the Usability of a technology in health. The linear relationship between the factors studied was positive and moderate between Familiarity and Usability, positive and strong between the Expertise and Attitude factors, both in relation to Usability, the Utility factor presented a negative and weak linear relationship with Usability, indicating that the factor Utility explains little of Usability.